Efficacies of Mineral Trioxide Aggregate and Bioceramic Root Canal Sealer with Two Types of Gutta-Percha toward the Apical Leakage - Christian Eka Pramudita; Bernard Ongki Iskandar; Wiena Widyastuti; Didi Nugroho Santosa (Faculty of Dentistry, Universitas Trisakti, 2020)
Background: Mineral trioxide aggregate (MTA) is the most widely used material in endodontics, and recently, it has been used as an endodontic sealer. Bioceramic (BC) is a newly developed material based on calcium silicate, which is already used as a biocompatible root canal obturation material to overcome the weakness of MTA. However, there have been no studies comparing the materials used to seal the root canal. Objective: This study aimed to determine the apical leakage differences between BC and MTA sealers with BC‑coated gutta-percha (GP) and conventional GP. Methods: In total, 40 mandibular premolars were cut coronally to 14 mm of working length. All samples were randomized and sorted into four groups: BC sealer with BC-coated GP, bioceramic sealer with conventional GP, MTA sealer with BC-coated GP, and MTA sealer with conventional GP. The samples were stored in an incubator, and nail varnish was applied to all root surfaces except for a 1 mm area from the apex. The samples were also soaked in methylene blue for 72 h before undergoing diaphanization. A stereomicroscope was used to measure the methylene blue penetration. All data were analyzed using analysis of variance. Results: There were significant differences in apical leakage between the BC and MTA sealers (P < 0.05). Conclusion: The BC sealer prevented apical leakage better than MTA. The BC-coated GP had better results than the conventional GP, but the differences were not significant, indicating that the choice of sealer is more important in preventing the apical leakage.